Changes in Serum Sphingomyelin After Roux-en-Y Gastric Bypass Surgery Are Related to Diabetes Status - Carlsson, Elin Rebecka; Grundtvig, Josefine Liv Gilling; Madsbad, Sten; Fenger, Mogens (Frontiers in Endocrinology, 2018)
Metabolic surgery is superior to lifestyle intervention in reducing weight and lowering glycemia and recently suggested as treatment for type 2 diabetes mellitus. Especially Roux-en-Y gastric bypass (RYGB) has been focus for much research, but still the mechanisms of action are only partly elucidated. We suggest that several mechanisms might be mediated by sphingolipids like sphingomyelin. We measured serum sphingomyelin before and up to two years after RYGB surgery in 220 patients, divided before surgery in one non-diabetic subgroup and two diabetic subgroups, one of which contained patients obtaining remission of type 2 diabetes after RYGB, while patients in the other still had diabetes after RYGB. Pre- and postoperative sphingomyelin levels were compared within and between groups. Sphingomyelin levels were lower in diabetic patients than in non-diabetic patients before surgery. Following RYGB, mean sphingomyelin concentration fell significantly in the non-diabetic subgroup and the preoperative difference between patients with and without diabetes disappeared. Changes in diabetic subgroups were not significant. Relative to bodyweight, an increase in sphingomyelin was seen in all subgroups, irrespective of diabetes status. We conclude that RYGB has a strong influence on sphingomyelin metabolism, as seen reflected in changed serum levels. Most significantly, no differences between the two diabetic subgroups were detected after surgery, which might suggest that patients in both groups still are in a “diabetic state” using the non-diabetic subgroup as a reference.